Remission structure in schizoaffective disorder - Syerikova, Olga I.; Skrynnyk, Olga V.; Serikova, Olga S. (Psychiatry, Neurology and Medical Psychology, 2020)
The article describes the comparative study of clinical and dynamic structure of remission in schizoaffective disorder (SAD), depending on its type. With the help of the clinical-psychopathological method with an analytical study of tavailable medical documentation and the method of follow-up examination, remissions were analyzed in 78 patients with SAD. In parallel, during the year, the severity of clinical manifestations of the disease was determined using psychometric scales (Young Mania Rating Scale – YMRS, Hamilton Depression Rating Scale – HDRS, Positive and Negative Symptoms Scale – PANSS). Several degrees of remission were identified – partial, complete clinical and complete functional remission. By partial remission, we understood a state when there was a pronounced reduction in clinical manifestations, but residual productive symptoms, poor insight and social maladjustment were observed. Complete clinical remission indicated the absence of any clinically significant signs, but social functioning was reduced. Full functional remission was characterized by the absence of any clinical signs and patient’s good social adaptation. All patients went through the stage of partial remission, however, about half of them (40 observations – 51.3%) went into complete clinical remission. Persistent partial remission which later did not transform into clinical remission was observed in 38 patients with SAD (48.7%). It was represented by the following syndromes — asthenic (28.9%), hypersthenic (23.8%), psychopathic (34.2%), residual delusional syndrome (13.1%). Complete functional remission was found in 19 patients (24.4%). The data obtained indicate that the longest and most complete remissions were observed in manic and depressive types of SAD compared with mixed ones. In the manic type of SAD complete functional remission was more common (12 cases – 38.7%), with the depressive type - complete clinical remission (8 patients – 32.0%), with the mixed type - partial remission (10 patients – 38.5%). Depending on the type of SAD remission there is a different risk of disease recurrence, therefore, the treatment and rehabilitation measures, the appointment of maintenance therapy should be differentiated.